Diabetology: Feature Papers 2022 - Clifton, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As Editor-in-Chief of the journal Diabetology, I am pleased to announce that the Special Issue "Diabetology: Feature Papers 2022" has now been published as a reprint. Diabetology (ISSN 2673-4540) is an international, peer-reviewed scientific open access journal that provides an advanced forum for studies related to the epidemiology, etiology, pathophysiology, pathogenesis, management, complications, and prevention of diabetes, including the molecular, biochemical, and physiological aspects of diabetes. In this Special Issue, "Feature Papers", we aimed to publish outstanding contributions in the main fields covered by the journal, which will make a great contribution to the community. This reprint covers the whole spectrum of diabetology from risk screening, risk markers, pathways of disease in type 1 diabetes and insulin treatment, and management of the disease and comorbidities.